Teacher Skills in Recognizing Children's Learning Preferences as Supporting the Diverse Learning Process in Early Childhood - Maharani Putri; Khanifah (International Journal of Educational Evaluation and Policy Analysis, 2024)
This research aims to investigate teachers' skills in recognizing children's learning preferences as a support for the diverse learning process in early childhood. Qualitative research methods were used to collect data through classroom observations, interviews with teachers, and analysis of documentation related to early childhood learning. Teachers who are sensitive to differences in learning preferences can optimize the learning process and increase children's participation and understanding. Teaching strategies that are inclusive and support the diversity of children's learning are the key to achieving effective learning goals.